Fiscal spillovers: The case of US corporate and personal income taxes - Madeline Hanson; Daniela Hauser; Romanos Priftis (Bank of Canada, 2021)
This paper extends the identification of unanticipated changes in average federal corporate and personal income tax rates in the United States, as proposed in Mertens and Ravn (2013), to the end of 2019, and assesses their propagation to economies with tight links to the US economy. While cuts in both taxes lead to significant short-run expansions in the US economy, their spillover effects on other countries differ markedly. A cut in corporate taxes can produce negative spillovers, indicating that the contractionary effects associated to the reallocation of investment and jobs by multinational firms outweigh the potential positive effects of increased demand for country-specific goods through trade with the US. The spillover effects of lower personal income taxes are more heterogeneous across countries but are, on average, expansionary, depending on the country-specific monetary policy stance.
Keywords: H20; E32; E62; F44; 330; Business fluctuations and cycles; Econometric and statistical methods; Exchange rateregimes; Fiscal policy; International topics